2011
DOI: 10.3109/03009742.2010.536163
|View full text |Cite
|
Sign up to set email alerts
|

The prothrombinase activity of FGL2 contributes to the pathogenesis of experimental arthritis

Abstract: This study demonstrates that the prothrombinase activity of mFGL2 contributes to the pathogenesis of experimental arthritis. These studies may have therapeutic implications for patients with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…FGL2 prothrombinase activity has been postulated to directly convert prothrombin to thrombin [22,23] and has been associated with fibrin deposition in some pathological processes [6,7,2426]. FGL2 also exists as a secretory molecule with immunoregulatory activity [12,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…FGL2 prothrombinase activity has been postulated to directly convert prothrombin to thrombin [22,23] and has been associated with fibrin deposition in some pathological processes [6,7,2426]. FGL2 also exists as a secretory molecule with immunoregulatory activity [12,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Functionally distinct from mFGL2, sFGL2 possesses abilities in immunomodulation and contradictory properties in tissue injuries [15, 19, 20]. Recently, a growing body of evidence indicated that FLG2 was involved in the pathogenesis of a variety of diseases such as pregnancy failure [21], tumor growth [22], viral infection [2325], allograft rejection [26], and autoimmune disorders [12, 27]. As the physiological function and the pathogenetic roles of mFGL2 have been well elucidated in some other papers [20, 28, 29], this mini-review will focus on recent progress about the signaling mechanism of sFGL2 in immunomodulation.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linking antibodies to CD200R1 also attenuates CIA [123], along with altered expression of cytokines associated with inflammatory pathology in this model. These observations were confirmed in independent studies [124] which compared CD200Fc with TNF inhibition (the current method of choice for refractory RA patients in the clinic). Inhibition mediated by CD200Fc in this system was comparable to that achieved by TNFRFc [125].…”
Section: Regulation Of Autoimmune Disease By Cd200:cd200rmentioning
confidence: 62%